Clostridium difficile phages: still difficult? - Hargreaves, Katherine R.; Clokie, Martha R. J. (Frontiers in Microbiology, 2014)
Phages that infect Clostridium difficile were first isolated for typing purposes in the 1980s, but their use was short lived. However, the rise of C. difficile epidemics over the last decade has triggered a resurgence of interest in using phages to combat this pathogen. Phage therapy is an attractive treatment option for C. difficile infection, however developing suitable phages is challenging. In this review we summarise the difficulties faced by researchers in this field, and we discuss the solutions and strategies used for the development of C. difficile phages for use as novel therapeutics. Epidemiological data has highlighted the diversity and distribution of C. difficile, and shown that novel strains continue to emerge in clinical settings. In parallel with epidemiological studies, advances in molecular biology have bolstered our understanding of C. difficile biology, and our knowledge of phage-host interactions in other bacterial species. These three fields of biology have therefore paved the way for future work on C. difficile phages to progress and develop. Benefits of using C. difficile phages as therapeutic agents include the fact that they have highly specific interactions with their bacterial hosts. Studies also show that they can reduce bacterial numbers in both in vitro and in vivo systems. Genetic analysis has revealed the genomic diversity among these phages and provided an insight into their taxonomy and evolution. No strictly virulent C. difficile phages have been reported and this contributes to the difficulties with their therapeutic exploitation. Although treatment approaches using the phage-encoded endolysin protein have been explored, the benefits of using “whole-phages” are such that they remain a major research focus. Whilst we don’t envisage working with C. difficile phages will be problem free, sufficient study should inform future strategies to facilitate their development to combat this problematic pathogen.